Construction monitoring and control of cable-stayed bridges without backstays - Xilong Zheng (Archives of Civil Engineering)
The cable-stayed bridge without backstays is an important branch of the cable-stayed bridge family. It tilts the bridge tower to one side and removes the backstay, using its own weight to balance the cable tension. It has the characteristics of novel structure and beautiful appearance and is highly favoured in urban construction both at home and abroad. In this paper, based on the construction of the main bridge of Jinzhou Bridge, a spatial model was established using finite element analysis software to simulate and analyse the construction process, with a focus on researching the construction control. Jinzhou Bridge has a novel structure and complex technology. The inclination angle of the bridge tower is the largest among its counterparts, and the difficulty of construction control is relatively high. This paper uses the adaptive control theory to control the construction of the main bridge of Jinzhou Bridge. During the construction process and the bridge state, the structure of Jinzhou Bridge is subject to reasonable stress and the bridge body is safe and reliable. The line shape of the main beam is basically smooth, further demonstrating the correctness of the construction control theory data.